‘It’s a wide cluster of noise’: experiencing and describing information from environmental sounds - Stewart-Robertson, Owen (Information Research an international electronic journal, 2025)
Introduction. Uses and applications of environmental sound recording are expanding rapidly, shaped by demands for understanding and documenting changing climates and resulting in the generation of massive quantities of data. Situations around the creation and processing of these recordings are complex, suggesting numerous information-related challenges. However, little information practices research has directly engaged with sounds or sound recording. Method. Extending information research around sounds and embodied/sensory experiences, this qualitative study involved data generated from semi-structured interviews, participant observation and discourse materials. Participants were researchers working with environmental sound recording from various fields. Analysis. Guided by situational analysis, an extension of grounded theory, analysis involved iterative coding, memo-writing and analytic mapping techniques. Results. Preliminary findings are presented in two themes: noise, as concept and object, is constituted through participants’ situated information practices; and identification and description of sounds is tied to subjective/embodied experiences and ways of knowing. Conclusions. The ways situated knowledge and experiences shape how information from environmental sounds is created, sought and shared blur boundaries between signal-noise and between information activities. Embodied engagements with and descriptions of environmental sounds suggest the complexities of understanding related information practices and highlight the various relationships involved in knowledge production through environmental sounds.